Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To complete the table for the graph given by the equation [tex]\(2x - y = 6\)[/tex], we need to find the values of [tex]\(y\)[/tex] that satisfy this equation for the given values of [tex]\(x\)[/tex].
Let's work through the calculation of [tex]\(y\)[/tex] step-by-step for each given [tex]\(x\)[/tex] value:
1. When [tex]\(x = -2\)[/tex]:
[tex]\[ 2(-2) - y = 6 \][/tex]
Simplifying this,
[tex]\[ -4 - y = 6 \][/tex]
Adding 4 to both sides,
[tex]\[ -y = 10 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -10 \][/tex]
Thus, [tex]\(A = -10\)[/tex].
2. When [tex]\(x = -1\)[/tex]:
Given that [tex]\(y = -8\)[/tex], it does not need further calculation.
3. When [tex]\(x = 0\)[/tex]:
[tex]\[ 2(0) - y = 6 \][/tex]
Simplifying this,
[tex]\[ 0 - y = 6 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -6 \][/tex]
Thus, [tex]\(B = -6\)[/tex].
4. When [tex]\(x = 1\)[/tex]:
Given that [tex]\(y = -4\)[/tex], it does not need further calculation.
5. When [tex]\(x = 2\)[/tex]:
[tex]\[ 2(2) - y = 6 \][/tex]
Simplifying this,
[tex]\[ 4 - y = 6 \][/tex]
Subtracting 4 from both sides,
[tex]\[ -y = 2 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -2 \][/tex]
Thus, [tex]\(C = -2\)[/tex].
Hence, the completed table for the graph [tex]\(2x - y = 6\)[/tex] is:
[tex]\[ \begin{tabular}{c|c|c|c|c|c} x & -2 & -1 & 0 & 1 & 2 \\ \hline y & -10 & -8 & -6 & -4 & -2 \\ \end{tabular} \][/tex]
Let's work through the calculation of [tex]\(y\)[/tex] step-by-step for each given [tex]\(x\)[/tex] value:
1. When [tex]\(x = -2\)[/tex]:
[tex]\[ 2(-2) - y = 6 \][/tex]
Simplifying this,
[tex]\[ -4 - y = 6 \][/tex]
Adding 4 to both sides,
[tex]\[ -y = 10 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -10 \][/tex]
Thus, [tex]\(A = -10\)[/tex].
2. When [tex]\(x = -1\)[/tex]:
Given that [tex]\(y = -8\)[/tex], it does not need further calculation.
3. When [tex]\(x = 0\)[/tex]:
[tex]\[ 2(0) - y = 6 \][/tex]
Simplifying this,
[tex]\[ 0 - y = 6 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -6 \][/tex]
Thus, [tex]\(B = -6\)[/tex].
4. When [tex]\(x = 1\)[/tex]:
Given that [tex]\(y = -4\)[/tex], it does not need further calculation.
5. When [tex]\(x = 2\)[/tex]:
[tex]\[ 2(2) - y = 6 \][/tex]
Simplifying this,
[tex]\[ 4 - y = 6 \][/tex]
Subtracting 4 from both sides,
[tex]\[ -y = 2 \][/tex]
Multiplying both sides by -1,
[tex]\[ y = -2 \][/tex]
Thus, [tex]\(C = -2\)[/tex].
Hence, the completed table for the graph [tex]\(2x - y = 6\)[/tex] is:
[tex]\[ \begin{tabular}{c|c|c|c|c|c} x & -2 & -1 & 0 & 1 & 2 \\ \hline y & -10 & -8 & -6 & -4 & -2 \\ \end{tabular} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.